24th World Congress of Dermatology. Issue 2 (March 2020) - Coyner, Theresa; Nicol, Noreen Heer; Inabinet, Robin; Jellerichs, Bradley; Aldredge, Lakshi
Abstract : ABSTRACT: The 24th World Congress of Dermatology was held in Milan, Italy, on June 11–15, 2019, under the auspices of the International League of Dermatological Societies. The Dermatology Nurses' Association and the British Dermatological Nursing Group, both sister societies of the International League of Dermatological Societies, coordinated a nursing scientific program and a half-day leadership meeting held during the World Congress. Overview of the nursing scientific program and outcomes of the half-day leadership meeting are described.